Mixed legume–grass seeding and nitrogen fertilizer input enhance forage yield and nutritional quality by improving the soil enzyme activities in Sichuan, China - Tahir, Muhammad; Wei, Xiao; Liu, Haiping; Li, Jiayi; Zhou, Jiqiong; Kang, Bo; Jiang, Dongmei; Yan, Yanhong (Frontiers in Plant Science, 2023)
Information regarding relationships among forage yield and soil enzymes of legume-grass mixtures under nitrogen (N) fertilization can guide decision making during sustainable forage production. The objective was to evaluate the responses of forage yield, nutritional quality, soil nutrients, and soil enzyme activities of different cropping systems under various N inputs. The alfalfa (Medicago sativa L.), white clover (Trifolium repens L.), orchardgrass (Dactylis glomerata L.), and tall fescue (Festuca arundinacea Schreb.) were grown in monocultures and mixtures (A1: alfalfa, orchardgrass, and tall fescue; A2: alfalfa, white clover, orchardgrass, and tall fescue) under three N inputs (N1: 150 kg ha˗1; N2, 300 kg ha˗1; and N3: 450 kg ha˗1) in a split plot arrangement. Results highlights that A1 mixture under N2 input had greater forage yield of 13.88 t ha˗1 yr˗1 than other N inputs, whereas A2 mixture under N3 input had greater forage of 14.39 t ha˗1 yr˗1 than N1 input but it was not substantial greater than N2 input (13.80 t ha˗1 yr˗1). The CP content of grasses monocultures and mixtures significantly (P < 0.05) increased with increase in the rate of N input, and A1 and A2 mixtures under N3 input had greater CP content of 18.91 and 18.94% DM, respectively, than that of grass monocultures under various N inputs. The A1 mixture under N2 and N3 inputs had substantial greater (P < 0.05) ammonium N content of 16.01 mg kg˗1 and 16.75 mg kg˗1, whereas A2 mixture under N3 had greater nitrate N content of 4.20 mg kg˗1 than other cropping systems under various N inputs. The A1 and A2 mixtures under N2 input had significant higher (P < 0.05) urease enzyme activity of 0.39 and 0.39 mg g˗1 24 h˗1, and hydroxylamine oxidoreductase enzyme activity of 0.45 and 0.46 mg g˗1 5 h˗1, respectively, than other cropping system under various N inputs. Taken together, growing legume-grass mixtures under N2 input is cost effective, sustainable, and eco-friendly which provide greater forage yield and improved nutritional quality by better utilization of resources.